Drug utilization in clinical conditions: an update on its essentials - Kumar, Ashok; Sattigeri, B. M.; Chauhan, Shefali (International Journal of Research in Medical Sciences, 2017)
Drug utilization studies may be defined as studies of the marketing, distribution, prescription and use of drugs in a society, with special emphasis on the resulting medical, social and economic consequences. Drug utilization studies can provide highly valuable information, at a reasonable price, on the costs and effects (harmful and beneficial) of drugs. Such studies make available much useful information including indirect data on morbidity, the pharmaceutical component of the treatment cost of an illness, therapeutic compliance, the incidence of adverse reactions, the effectiveness of drug consumption and the choice of comparators. This information can be of great use in the subsequent elaboration of pharmacoeconomy studies, or in the selection of problematic areas in which these studies may be applied. Pharmacoeconomy studies, in turn, can be used to discover the economic repercussions of inappropriate prescribing and to quantify the cost effectiveness of various therapeutic interventions. The use of drug utilization studies in conjunction with pharmacoeconornic analysis can result in more cost effective utilization of medicines and a better utilization of pharmacoeconomy methods, both of which contribute to a more rational use of drugs.